2002
DOI: 10.1182/blood.v99.6.1922
|View full text |Cite
|
Sign up to set email alerts
|

Does treatment with intermittent infusions of intravenous anti-D allow a proportion of adults with recently diagnosed immune thrombocytopenic purpura to avoid splenectomy?

Abstract: This study explored whether repeated infusions of intravenous anti-D could allow adults with recently diagnosed immune thrombocytopenic purpura (ITP) who had failed an initial steroid course to postpone and ultimately avoid splenectomy. Twenty-eight Rh ؉ , nonsplenectomized adults with ITP diagnosed within 1 to 11 months and platelet counts 30 ؋ 10 9 / L (30 000/L) or below were enrolled. Anti-D was infused whenever the platelet count decreased to 30 ؋ 10 9 /L (30 000/ L) or below. "Response" was defined as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 21 publications
1
53
0
3
Order By: Relevance
“…Standard first-line treatments for ITP include prednisone [3][4][5][6][7], intravenous gamma globulin (IVIg) [6], and intravenous anti-D [8][9][10][11][12][13]. If ITP is persistent despite first-line therapies, then splenectomy is usually the second-line approach in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Standard first-line treatments for ITP include prednisone [3][4][5][6][7], intravenous gamma globulin (IVIg) [6], and intravenous anti-D [8][9][10][11][12][13]. If ITP is persistent despite first-line therapies, then splenectomy is usually the second-line approach in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood ITP is typically a disease of acute onset; more than 80% of children will have a spontaneous and permanent remission within 1 year of onset [2]. In contrast, adults tend to have more persistent ITP [3], although recent studies suggest that there is a tendency for certain patients to improve with time [3][4][5][6]. Rarely, life-threatening bleeding occurs, with intracranial hemorrhage being the principle cause of death [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is common for children, many of whom will remit over time, and one single-arm prospective trial suggested that 40% of adults who failed an initial course of steroids could avoid splenectomy by intermittent treatment with anti-D. 34 A multi-institutional, randomized trial was conducted to compare "standard management" (oral steroids followed by early splenectomy) to aggressive anti-D for adults with ITP. 35 In this trial, treatment with anti-D was able to delay, but not avoid, splenectomy.…”
Section: Clinical Management Of Itp In the 21st Centurymentioning
confidence: 99%